ANALISIS POTENSI WISATA BAHARI DI PULAU KERAYAAN KABUPATEN KOTABARU - Dafiuddin Salim; Rochgiyanti Rochgiyanti; Syahlan Mattiro (Fish Scientiae, 2019)
This study aims to identify and develop the potential of marine tourism in the Kerayaan Island. Data analysis is done with based on the validity of data obtained fromthe field observations which then processed and discussed in a descriptive. The results show the potential of coral reefs as marine tourism on the island is quite extensive and is categorized as still good with the biodiversity of reef fish and marine life high. Physical chemical conditions of the waters are still good and according to the criteria of quality standards for marine tourism and supported its presence among the Makassar Strait and the Java Sea as well as a Coral Triangle World (Coral Triangle). With such a location, coral reef ecosystems and their biota have very close bioecological connectivity with other areas, especially other islands.